Co-design for democratising and its risks for democracy. Issue 3 (2nd July 2020) - Del Gaudio, Chiara; Franzato, Carlo; de Oliveira, Alfredo Jefferson
ABSTRACT: This paper reflects on the co-design approach for catalysing and fostering participatory democracy and the redistribution of power exercise within the urban space, particularly when it is practiced in conflict-affected urban areas. Upon applying co-design dynamics, designers give rise to new possibilities for power exercise whose existence they may be unaware of, and that can be appropriated by actors striving against the main principles of participatory democracy. Due to the multifaceted essence of co-design and to the complex nature of the context, when opening up the possibility of collaboration in a design process undertaken within the urban space, it becomes impossible to determine who is going to contribute to the co-design process and to acknowledge the specificity of each participant's contribution. Two cases help to reflect on the challenges that co-design dynamics may bring to participatory democracy and they shed light on informality and tactics as potential features of a co-design practice capable of preventing or reducing the influence of anti-democratic forces on the design process.